A atividade editorial intramuros como prática cultural de extensão universitária - Rubin, María José (Universidad Nacional del Litoral, 2019)
This article reflects on the activity of the Taller Colectivo de Edición (TCE) as an extension course of the Faculty of Philosophy and Letters of the UBA and its specificity as a work instance that brings into play tools of editorial work. This pedagogical proposal that has been developed since 2008 seeks to enable a space and a practice that will recover the experiences, knowledge and critical capacity of the workshops to become a working group with a view to publishing a magazine. Based on the work carried out by the TCE, the present work intends to recover the editorial activity within the framework of the university extension and the products that result from it as a source for the construction of a memory regarding the intramural cultural practice that is in articulation with the university. This, in turn, raises the need to redefine the concept of Traditional Edition within the framework of its work in territory from the perspective of university extension.